Zależy na jakich ułamkach Ci się lepiej liczy, dla odpowiedzi będę używał ułamków zwykłych.
[tex](-5,5+\frac{1}{4})*(-2)=(-5\frac{2}{4}+\frac{1}{4})*(-2)=-5\frac{1}{4}*(-2)=10\frac{2}{4}=10\frac12[/tex]
[tex]-1\frac{1}{3}*(-0,3)^2=-\frac43*0,09=-\frac43*9*0,01=-4*3=-12\\[/tex]
[tex]-4,9*(\frac17)^2-0,02=-4\frac9{10}*\frac{1}{49}-\frac2{100}=-\frac{49}{10}*\frac{1}{49}-\frac1{50}=-\frac{1}{10}-\frac{1}{50}=-\frac{5}{50}-\frac{1}{50}=-\frac{6}{50}[/tex]
[tex]{[2\frac23-1\frac13*(-\frac14)]}*3,5={[1\frac13*(-\frac14)]}*3,5={[\frac43*(-\frac14)]}*3\frac12=-\frac13*\frac72=-\frac76=-1\frac16\\[/tex]
[tex](-\frac35)^2:(-3)=\frac9{25}:(-3)=\frac9{25}*(-\frac13)=-\frac3{25}[/tex]
[tex]-0,5-(-11)=-\frac12+11=10\frac12[/tex]